Nitric Oxide Pathways in Neurovascular Coupling Under Normal and Stress Conditions in the Brain: Strategies to Rescue Aberrant Coupling and Improve Cerebral Blood Flow - Lourenço, Cátia F.; Laranjinha, João (Frontiers in Physiology, 2021)
The brain has impressive energy requirements and paradoxically, very limited energy reserves, implying its huge dependency on continuous blood supply. Aditionally, cerebral blood flow must be dynamically regulated to the areas of increased neuronal activity and thus, of increased metabolic demands. The coupling between neuronal activity and cerebral blood flow (CBF) is supported by a mechanism called neurovascular coupling (NVC). Among the several vasoactive molecules released by glutamatergic activation, nitric oxide (•NO) is recognized to be a key player in the process and essential for the development of the neurovascular response. Classically, •NO is produced in neurons upon the activation of the glutamatergic N-methyl-D-aspartate (NMDA) receptor by the neuronal isoform of nitric oxide synthase and promotes vasodilation by activating soluble guanylate cyclase in the smooth muscle cells of the adjacent arterioles. This pathway is part of a more complex network in which other molecular and cellular intervenients, as well as other sources of •NO, are involved. The elucidation of these interacting mechanisms is fundamental in understanding how the brain manages its energy requirements and how the failure of this process translates into neuronal dysfunction. Here, we aimed to provide an integrated and updated perspective of the role of •NO in the NVC, incorporating the most recent evidence that reinforces its central role in the process from both viewpoints, as a physiological mediator and a pathological stressor. First, we described the glutamate-NMDA receptor-nNOS axis as a central pathway in NVC, then we reviewed the link between the derailment of the NVC and neuronal dysfunction associated with neurodegeneration (with a focus on Alzheimer’s disease). We further discussed the role of oxidative stress in the NVC dysfunction, specifically by decreasing the •NO bioavailability and diverting its bioactivity toward cytotoxicity. Finally, we highlighted some strategies targeting the rescue or maintenance of •NO bioavailability that could be explored to mitigate the NVC dysfunction associated with neurodegenerative conditions. In line with this, the potential modulatory effects of dietary nitrate and polyphenols on •NO-dependent NVC, in association with physical exercise, may be used as effective non-pharmacological strategies to promote the •NO bioavailability and to manage NVC dysfunction in neuropathological conditions.